2022
DOI: 10.31234/osf.io/qnda3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Breaking reality’s constraints on motivated cognition

Abstract: Wishful thinking is constrained by reality; people cannot believe the utterly implausible simply because they want to. Here, we uncover an exception to this basic principle of motivated cognition. We show that one goal in particular---the goal to advocate---systematically biases judgments in spite of strong countervailing evidence. This is more than a harmless delusion. Advocacy goals lead to greater endorsement of far-fetched `crackpot' theories (Study 5), and impede performance in negotiations (Study 6). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Though subtle, these shifts in belief persist in the face of accuracy incentives and prompts to be wary of biasing oneself. Strohminger & Melnikoff (2022) further showed that advocacy goals shifted beliefs about the truth of far-fetched "crackpot" theories and claims that were inconsistent with strong counter-evidence provided to participants.…”
Section: Automaticitymentioning
confidence: 95%
“…Though subtle, these shifts in belief persist in the face of accuracy incentives and prompts to be wary of biasing oneself. Strohminger & Melnikoff (2022) further showed that advocacy goals shifted beliefs about the truth of far-fetched "crackpot" theories and claims that were inconsistent with strong counter-evidence provided to participants.…”
Section: Automaticitymentioning
confidence: 95%